p.Gly743Val Mutation in COL4A1 Is Responsible for Familial Porencephaly and Severe Hypermetropia - Scoppettuolo, Pasquale; Ligot, Noémie; Wermenbol, Vanessa; Van Bogaert, Patrick; Naeije, Gilles (Frontiers in Neurology, 2020)
We reported a COL4A1 gene variant, p.Gly743Val, responsible for familial porencephaly and severe hypermetropia. As for other COL4A1 mutation and families, this variant is segregated in an autosomal dominant manner and associated with variable expressivity.